DISCOVERING SLICES FROM A 3-DIMENSIONAL MRI DATA SET USING SPATIAL TRANSFORMATION - RAHIMA SULTHANA.M.Z; SP.CHOKKALINGAM (International Journal of Pharma and Bio Sciences, 2015)
The term MRI literally refers to the Magnetic Resonance Imaging. The MRI is a type of scan which produces a high quality images in multiple planes or directions to view the internal structures of the body. It is powerful diagnostic tool which uses a strong magnetic field and radio waves to produce such images. The slicing is a process of dividing the single 2D image layout into multiple images to view the different dimensions of the image. In this MRI scan of human brain, the 3D image of brain is partitioned into slices, so that it is possible to view the different sequential layers of the brain. Using MRI, the brain can be viewed in ways such as 1.Coronal plane 2.Horizontal plane 3.Sagittal plane.In this paper we will see which technique can be possibly implemented for extracting slices from the 3-Dimensional MRI data of brain.